Critical Considerations for Physical Literacy Policy in Public Health, Recreation, Sport, and Education Agencies. Issue 4 (2nd October 2017) - Dudley, Dean; Cairney, John; Wainwright, Nalda; Kriellaars, Dean; Mitchell, Drew
ABSTRACT: The International Charter for Physical Education, Physical Activity, and Sport clearly states that vested agencies must participate in creating a strategic vision and identify policy options and priorities that enable the fundamental right for all people to participate in meaningful physical activity across their life course. Physical literacy is a rapidly evolving concept being used in policy making, but it has been limited by pre-existing and sometimes biased interpretations of the construct. The aim of this article is to present a new model of physical literacy policy considerations for key decision makers in the fields of public health, recreation, sport, and education. Internationally debated definitions of physical literacy and the wider construct of literacy were reviewed in order to establish common pillars of physical literacy in an applicable policy model. This model strives to be consistent with international understandings of what "physical literacy" is, and how it can be used to achieve established and developing public health, recreation, sport, and educative goals.